PENTINGNYA HUMAN RELATION YANG DILAKUKAN OLEH KEPALA KELURAHAN TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN (Studi Kasus Pada Kel. Kademangan Kec.Kademangan Kota Probolinggo) - Bambang Lasmono (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
The instruments are elements of the Village Head, elements of the village apparatus, elements of the Village Head, RT heads and RW heads, elements of the PKK management, youth organizations and existing organizations, elements of community leaders, and elements of the relevant parties. The results of the data analysis can be stated that the Human Relations carried out by the Village / Kelurahan Head on the participation of village communities in socioeconomic and socio-cultural development in the study object is worth more than enough. Information on table 1: A = Level of Human Relations conducted by the Head of Kelurahan in the Study Object, B = The level of community participation in socioeconomic and socio-cultural development in the study subject. Based on the results of analysis and interpretation of data, it can be argued that the Human Relations conducted by the Village Chief in the object of study, apparently have a relationship to citizen participation in socio-economic and cultural development. However, based on the results of the analysis and interpretation of data as stated that the Human Relations conducted by the Village Head in the object of study, apparently still not effective, this can be proven by finding several problems and solving some problems.